On slice hyperholomorphic fractional Hardy spaces. Issue 17 (15th September 2017) - Alpay, Daniel; Colombo, Fabrizio; Sabadini, Irene
Abstract: In this paper we introduce and study the fractional Hardy spaces of the half space and of the unit ball in the quaternionic setting. In particular, we discuss their properties of invariance and of factorization in terms of functions in the Hardy space of the half space in the first case, and in terms of a suitable reproducing kernel Hilbert space in the case of the unit ball.